An integrated energy-efficient electrochromic device for salt water purification. Issue 66 (23rd July 2020) - Silambarasan, Krishnamoorthy; Qin, Tengteng; Liu, Xiaoqiang; Zhou, Yanmei; Alwarappan, Subbiah
Abstract : Chemically assisted reverse dual ion electrochromic desalination device assembly for energy-efficient salt removal from salt water. Abstract : Herein, we report a multifunctional device with an integrated energy-desalination-smart electrochromic display in one single cell. Specifically, a novel chemically assisted electrochromic desalination set-up was demonstrated using a Prussian blue cathode and an anode comprising Ag or a redox polymer film in salt water without any external electrical energy usage.